Putting the “Fun” in Fundamentalism: Religious Nationalism and the Split Self at Hindutva Summer Camps in the United States - Falcone, Jessica Marie (Ethos, 2012)
Some Hindu immigrants to America – those who subscribe to Hindutva values – desire full rights and recognition in their adopted homeland even as they simultaneously demand that so-called “migrants” to India (that is, Muslims and Christians whose communities have flourished in India for hundreds of years) acquiesce to their vision of India as a “Hindu state.” In an American racial landscape that structurally privileges whites, I argue that the cultural categorization of Hindu immigrants into a “lesser-than-whites” minority has only served to fuel the growth of Hindu supremacist groups in the United States. In this article, I draw on fieldwork with two Hindu American summer camps in order to show that some Hindu immigrants misrecognize and repress their own current alienation in a manner that has subsequently aggravated latent antipathies towards Muslim and Christian communities in India. [religion, alienation, ethnicity, Hinduism, diaspora, nationalism]